The Perspective of Wendu Coastal Fishermen’s on The Presence of Sawfish (Pristis spp.) - Sianturi, Reny; Amir, Astaman (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Indonesia is the world's largest producer and catcher of sharks and rays (Chondrichthyans class). Saw Stingrays (Pristis spp.) have full protection status. Anoxypristis cuspidata is a type of Saw Stingray which is predominantly caught as bycatch from nets and fishing gear by traditional fishermen operating around the waters of Merauke, Papua. One of the determinants of the success of saw stingray conservation is human resources which can be seen from their knowledge and perspective on the existence of saw stingrays. This study aims to determine the perspective of Wendu coastal fishermen on the existence of saw stingrays. This research was conducted in June 2021-March 2022. There were 92 samples in this study, using the non-probability sampling method. The type of non-probability sampling used in this study is purposive sampling. The data analysis technique was carried out using the qualitative data analysis model of Miles and Huberman. Most of the respondents saw saw stingrays 1-2 times in their lifetime. According to the perspective of Wendu coastal fishermen, the number of saw rays decreased and the size of the saw rays decreased. Most still think that saw stingrays can be used either for consumption or for sale.